2020
DOI: 10.1021/acsomega.9b04355
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Fabrication of Flower-Shaped Au–Cu Nanostructures Using a Deep Eutectic Solvent and Their Performance in Surface-Enhanced Raman Scattering-Based Molecular Sensing

Abstract: Controlled synthesis of anisotropic bimetallic nanostructures with tunable morphology is of great current interest for their applications in surface-enhanced Raman scattering (SERS), plasmonics, and catalysis. Despite huge effort that has been devoted so far, fabrication of bimetallic nanostructures with controlled morphology and size remained to be a great challenge, especially when their shapes are anisotropic. Here, we report a facile, one-step synthetic approach for the fabrication of anisotropic bimetalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…It can be explained that a higher redox potential of Au 3+ than that of Ag + (Au 3+ /Au = 1.002 V and Ag + /Ag = 0.80 V) is the driving force for the formation of Au rich Au–Ag alloy NPs. 27,28…”
Section: Resultsmentioning
confidence: 99%
“…It can be explained that a higher redox potential of Au 3+ than that of Ag + (Au 3+ /Au = 1.002 V and Ag + /Ag = 0.80 V) is the driving force for the formation of Au rich Au–Ag alloy NPs. 27,28…”
Section: Resultsmentioning
confidence: 99%
“…[ 77 ] The Au 4f XPS survey spectra exhibited two significant peaks at ≈83.5 and ≈87.4 eV corresponding to the Au 4f 7/2 and 4f 5/2 characteristic signals and 1.14 eV for FWHM value of Au peak, respectively. [ 78,79 ] In addition, the high‐resolution spectra of Co 2p, O 1s, Ag 3d, and Au 4f regions of Au@ZIF‐67‐CO, Ag@ZIF‐67‐CO, and ZIF‐67‐CO are presented in Figure S5 (Supporting Information). The XPS spectra of Au@ZIF‐67‐CO and Ag@ZIF‐67‐CO demonstrate that the Co and O elements of ZIF‐67‐CO are maintained after the electrodeposition or chemical grafting process.…”
Section: Resultsmentioning
confidence: 99%
“…They achieved a 50-fold enhancement in SERS spectra with 10% Ag-Cu alloy microflowers, which supersedes the efficiency of pure Au-Ag MFs [ 180 ]. Bimetallic nanostructures with tunable morphology are of current interest in plasmonics, catalysis and SERS [ 175 ]. In their study, Siva et al fabricated gold−copper nanostructures (Au−Cu NSs) of 200–300 nm size range and revealed a high SERS signal for crystal violet with EF as high as 10 6 and the ability to detect crystal violet (CV) molecules of concentrations as low as 10 −10 M. In addition, Rao et al showed that modification of Cu substrate with Ag is highly dependent on the concentration of Ag [ 178 ].…”
Section: Coppermentioning
confidence: 99%